2013
DOI: 10.1111/ijd.12091
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based management of primary and localized Merkel cell carcinoma: a review

Abstract: For primary tumors without evidence of organ metastases, surgical excision should be the primary therapy. Owing to the high rate of local metastases, a safety margin of at least 2 cm should be considered. In situations where small, localized tumors and/or special locations necessitate a smaller safety margin, compensation by complete histological examination of the excision margins and perhaps adjuvant radiation therapy should be undertaken. The literature states that benefits of Mohs micrographic surgery (ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…Furthermore, in the literature, there is no formal evaluation of appropriate excision margins and the risk of recurrence. However, the local recurrence rate is significantly higher with small excisions and is particularly high in case of positive surgical resection margins 105,115 (that is, if tumour cells are present at the edge of the excised tissue). The National Comprehensive Cancer Network (NCCN) and the European Association of Dermato-Oncology (EADO)–European Organisation for Research and Treatment of Cancer (EORTC) guidelines recommend a 1–2 cm excision margin down to the muscle fascia or the pericranium (the membrane that externally covers the skull), regardless of tumour size 81,82,116 .…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the literature, there is no formal evaluation of appropriate excision margins and the risk of recurrence. However, the local recurrence rate is significantly higher with small excisions and is particularly high in case of positive surgical resection margins 105,115 (that is, if tumour cells are present at the edge of the excised tissue). The National Comprehensive Cancer Network (NCCN) and the European Association of Dermato-Oncology (EADO)–European Organisation for Research and Treatment of Cancer (EORTC) guidelines recommend a 1–2 cm excision margin down to the muscle fascia or the pericranium (the membrane that externally covers the skull), regardless of tumour size 81,82,116 .…”
Section: Managementmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) and the European Association of Dermato-Oncology (EADO)–European Organisation for Research and Treatment of Cancer (EORTC) guidelines recommend a 1–2 cm excision margin down to the muscle fascia or the pericranium (the membrane that externally covers the skull), regardless of tumour size 81,82,116 . When functional considerations are important, excision can be performed with microscopically controlled surgery and complete histological inspection of the margins of the excised material to confirm complete resection of the tumour can be considered, but experience is limited in MCC 115,117,118 . Of note, the safety margin is intended to remove microscopic satellite metastases rather than to ensure clear resection margins of the primary tumour 81,82 .…”
Section: Managementmentioning
confidence: 99%
“…Indeed, administration of PPARc agonists to psoriatic patients associates with amelioration of symptoms and skin lesions (Table S1). The systemic administration of troglitazone and pioglitazone improved skin lesions in psoriatic patients (52)(53)(54)(55), whereas rosiglitazone was ineffective either systemically or topically underlining how different ligands lead to diverse biological effects (56,57).…”
Section: Psoriasismentioning
confidence: 99%
“…Currently, adjuvant RT is advocated because MCC has a high incidence of nodal and metastatic disease. 27,28 A previously unaddressed question was whether RT was beneficial in those patients specifically known to be node negative. Our study found that there was no statistical survival advantage to giving adjuvant RT to patients with a negative SLNB.…”
Section: Commentsmentioning
confidence: 99%
“…In their review, Ellis and Davis suggested that RT should be optional for patients at lowest risk for locoregional failure, including immunocompetent patients with primary tumors less than or equal to 1 cm with no adverse histologic features, whose WLEs show clear margins and whose SLNB is negative. 28,29 Chemotherapy has traditionally been reserved as more of a palliative and salvage option, although MCC is considered to be chemosensitive. Although high remission rates of up to 70% are seen, there has been no survival benefit.…”
Section: Commentsmentioning
confidence: 99%